2024
DOI: 10.1002/advs.202308698
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional Therapeutic Strategy Using P7C3 as A Countermeasure Against Bone Loss and Fragility in An Ovariectomized Rat Model of Postmenopausal Osteoporosis

Fei Wei,
Megan Hughes,
Mahmoud Omer
et al.

Abstract: By 2060, an estimated one in four Americans will be elderly. Consequently, the prevalence of osteoporosis and fragility fractures will also increase. Presently, no available intervention definitively prevents or manages osteoporosis. This study explores whether Pool 7 Compound 3 (P7C3) reduces progressive bone loss and fragility following the onset of ovariectomy (OVX)‐induced osteoporosis. Results confirm OVX‐induced weakened, osteoporotic bone together with a significant gain in adipogenic body weight. Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 259 publications
(322 reference statements)
1
0
0
Order By: Relevance
“…Yadav et al found that reducing 5-HT levels with synthetic molecular inhibitors could effectively prevent bone loss typically induced by ovariectomy (OVX) ( Yadav et al, 2010 ). Several studies, reinforcing our findings, indicate that the genus Ruminococcaceae UCG014 plays a beneficial role in the management and improvement of OP ( Liu et al, 2020 ; Ling et al, 2021 ; Wei et al, 2024 ). This beneficial effect aligns with recent research on strontium (Sr), a bioactive element recognized for its potential to enhance bone quality ( Schrooten et al, 2003 ; Wornham et al, 2014 ).…”
Section: Discussionsupporting
confidence: 86%
“…Yadav et al found that reducing 5-HT levels with synthetic molecular inhibitors could effectively prevent bone loss typically induced by ovariectomy (OVX) ( Yadav et al, 2010 ). Several studies, reinforcing our findings, indicate that the genus Ruminococcaceae UCG014 plays a beneficial role in the management and improvement of OP ( Liu et al, 2020 ; Ling et al, 2021 ; Wei et al, 2024 ). This beneficial effect aligns with recent research on strontium (Sr), a bioactive element recognized for its potential to enhance bone quality ( Schrooten et al, 2003 ; Wornham et al, 2014 ).…”
Section: Discussionsupporting
confidence: 86%